2014
DOI: 10.5897/jeif2013.0548
|View full text |Cite
|
Sign up to set email alerts
|

The effect of currency devaluation on output: The case of ethiopian economy

Abstract: This paper assesses the short and long run effects of currency devaluation on output growth in Ethiopia. The study is conducted by using quarterly time series data over the period ranging from 1998.Q1 to 2010.Q4 and employing a vector auto regression (VAR) model. By controlling the monetary and fiscal policies, it is found that currency devaluations are contractionary in the long run and neutral in the short-run. Other results are that monetary policy has positive effect on output growth, while total governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Our results are also in line with those of Shahbaz et al. (2012), who found that the effect of real devaluation on economic growth is contractionary in Pakistan and Ayen (2014), who found currency devaluations to be contractionary in the long run and neutral in the short run in Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results are also in line with those of Shahbaz et al. (2012), who found that the effect of real devaluation on economic growth is contractionary in Pakistan and Ayen (2014), who found currency devaluations to be contractionary in the long run and neutral in the short run in Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to the findings of several earlier studies, such as Nusair (2021) for Malaysia, in which appreciations have no long-run effect on output depreciations are contractionary. Our results are also in line with those of Shahbaz et al (2012), who found that the effect of real devaluation on economic growth is contractionary in Pakistan and Ayen (2014), who found currency devaluations to be contractionary in the long run and neutral in the short run in Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations